Kata Serapan Dalam Bahasa Dawan (Uab Meto) Pada Masyarakat Nano Kecamatan Kualin Kabupaten Timor Tengah Selatan: Indonesia - Kase, Wanti E.; Bani, Ona D.; Kolnel, Arnot A. (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
This study aims to find out the Thesis entitled "Loan Words in the Dawan Language (Uab Meto) in the Nano Community, Kualin District, South Central Timor Regency. The problem in this study is what are the loan words in the Dawan language (Uab Meto). The purpose of this study is to find out the loan words in the Dawan language (Uab Meto). The benefits of this study are to expand the author's knowledge about loan words in the Dawan language. The theory used in this study is the theory of structural linguistics. Where the study or analysis of language must be descriptive, language has its own rules. The method used in this study is a qualitative descriptive method. Based on the results of this study, several loan words were found in the Dawan language, namely 1. Direct loan words in the Dawan language such as the words forok, and oto; 2. loan words that change in the Dawan language such as the words klas, bol, anin, sulat, kofi, tasu botil, lok, fatu, loko, lelken, beskoet, mistal, los, and kuk; 3. Slang loan words in the language dawan such as the words bestie, kulot, krop, and kibol 4. loan words in the dawan language such as the words skol, nalkoba, covid-19, hp, pupuk, lokte and lesa.